Comparison of psychological well-being, hope, and health concern in leukemia patients before and after receiving stem cells - Tahereh Yavari; Amiryousef Zahedi; Nima Movahednia; Negin Hajhamidiasl; Fariba Gheisvandi; Fatemeh Sheyni (Journal of Family Medicine and Primary Care)
Objectives: The aim of this study was to compare psychological well-being, hope, and health concerns in leukemia patients before and after receiving stem cells. Methods: The statistical population of the present study consisted of leukemia patients in Tehran, and the research sample was among the patients referred to the Bone Marrow Transplant Center of Shariati Hospital in Tehran, and they were placed in two experimental and control groups (15 people in each group), which were selected by purposive sampling method. Results: To collect the data for the research, three psychological well-being questionnaires were used by Riff (2002), Schneider's Hope Scale (SHS), and Schneider's (1991) Health Concern Questionnaire (HCQ). To analyze the data in this research, according to the “pre-test-post-test design with the control group,” covariance analysis was used. Conclusion: Based on the research findings, it was concluded that receiving stem cells increases hope and psychological well-being in leukemia patients and significantly reduces health concerns.